Pengaruh Implementasi Strategi Marketing Funnel Terhadap Penjualan Produk Graha Office - Georgius Erlangga Mahendra Yudantha; Dwi Sukma Donoriyanto (International Forum of Researchers and Lecturers, 2024)
In today's fiercely competitive digital business landscape, companies like Graha Office must leverage marketing funnels to enhance their sales strategies. This study delves into the implementation of funnel marketing strategies within Graha Office services, examining how funnel stages, market phases, clicks, impressions, and CTR correlate with product sales. The findings indicate a relationship between funnel stages and sales, although cautious interpretation of causality is warranted. This research establishes a foundation for the company's future actions using statistical methods, particularly via linear regression with an output of coefficient t count -2.179 < t table 2.119 (H2 accepted). However, it underscores our limitations in comprehending more intricate cause-and-effect relationships within the real world.